The importance of physical treatment in children underwent craniosynostosis surgery in the first year of life - Pavićević, Danijela; Milošević, Jelena; Petrović Marković, Ivana; Milenković, Zoran; Parezanović Ilić, Katarina (Vojnosanitetski pregled, 2021)
Background/Aim. Craniosynostosis is a condition that occurs intrauterine or develops in the infant period, and represents premature fusion of cranial sutures. This fusion of sutures limits the normal cranium development and leads to disorder in the phase of rapid growth and development of the brain. Creation of craniosynostoses is associated with an increased incidence of developmental delay during the breastfeeding period. Craniosynostoses are treated by surgery. The role of a physiatrist is to postoperatively assess psychomotor development and implement habilitation treatment. The aim of this study was to determine distribution of the type of craniosynostoses according to the age and gender of patients, effectiveness of habilitation treatment and to estimate the somatosensory evoked potential in the preoperative and postoperative period in children who underwent craniosynostosis surgery in the first year of life. Methods. The study was designed as a retrospective research. The data were collected from medical records of 51 children with craniosynostoses and delay in psychomotor development who underwent surgical intervention. The children included in this study, during follow-up, were involved in the habilitation treatment. Results. An early diagnosis and surgical intervention had a favorable effect on the development of motor function in children with craniosynostoses. The importance of stimulation treatment in the postoperative period was also proved for achievement of an adequate degree of motor development in children in relation to age. The results of our study confirmed the results obtained in previously published studies that the children who did not undergo surgery and start with the habilitation treatment immediately after it, had delay in psychomotor development of moderate degree. Conclusion. Habilitation treatment significantly reduced the deviations in psychomotor development of children with craniosynostoses if it started immediately after the surgical procedure.
Keywords: craniosynostoses; skull; infant; psychomotor disorders; evoked potentials; somatosensory physical therapy modalities